EQUIVALENT CIRCUIT SIMULATION OF TWO-DEGREE OF FREEDOM VIBRO-IMPACT SYSTEM WITH GAP - LIU RuiJia; WANG Zheng; LUO Fan (Jixie qiangdu)
In mechanical systems, the gap between mechanical components causes nonlinear elastic collisions during their movement. Taking the two-degree of freedom vibro-impact system with gap as the research object, the mathematical model was established and the numerical simulation analysis was carried out in Matlab software. Based on this, the application of function generators, resistors, capacitors, operational amplifiers and oscilloscopes and other analog electronic components in Multisim software to establish the equivalent circuit model for simulation analysis. The results show that the simulation results of equivalent circuit are consistent with those of numerical simulation analysis.The difference is that the equivalent circuit simulation not only has faster and more efficient operation, but also can realize dynamic parameter adjustment and conversion analysis under different modes. The Equivalent circuit simulation provides a reference method for the dynamics research of nonlinear vibration system.